Pengaruh Pemberian Seduhan Daun Kelor pada Ibu Hamil Terhadap Peningkatan Kadar Haemoglobin - Susanti, Evi; Febriyanti, Hellen; Sagita, Yona Desni; Sanjaya, Riona (Journal of Current Health Sciences, 2021)
Anemia is a condition in which the levels of hemoglobin and erythrocytes are lower than normal. To treat anemia by means of pharmacological or non-pharmacological, non-pharmacological methods that can be done by consuming boiled Moringa leaves. Moringa leaves are a source of protein, vitamin A and vitamin C as well as minerals (iron and calcium, as well as a source of vitamin B. It has a low fat content. The purpose of this study was to determine the effect of giving Moringa leaf decoction to pregnant women on increasing hemoglobin levels at UPT Puskesmas Kenali District Belau of West Lampung Regency in 2021. This type of research is quantitative with a quasi-experimental design and a two group pre-test and post-test design approach. The population / subjects taken in this study were pregnant women with a sample of 15 respondents. The object of this research is the provision of Moringa leaf decoction and hemoglobin levels. This research was carried out at the UPT Puskesmas Kenali, Belalau District, West Lampung Regency in December 2021. Data collection used an observation sheet. Data analysis was univariate and bivariate (t test). The results showed that the average Hb level before being given Fe tablets and Moringa leaf decoction to pregnant women was 10.4 g/dl and the Hb level after being given Fe tablets and Moringa leaf decoction to pregnant women was 11.5 g/dl. . The average Hb level before being given Fe tablets was 10.4 g/dl, and the Hb level after being given Fe tablets was 10.8 g/dl. There is an effect of giving Moringa leaf decoction to pregnant women on increasing hemoglobin levels at the UPT Puskesmas Kenali, Belalau District, West Lampung Regency in 2021 (p-value = 0.000). Suggestion Provide information to pregnant women about preventing and anticipating anemia by consuming boiled Moringa leavesAbstrak: Anemia merupakan suatu keadaan dimana kadar hemoglobin dan eritrosit lebih rendah dari normal, dapat ditangani dengan cara non farmakologi, seperti mengkonsumsi seduhan daun kelor. Daun kelor merupakan sumber protein, vitamin A dan vitamin C serta mineral (besi dan kalsium, juga sumber vitamin B. Tujuan penelitian ini diketahui pengaruh pemberian seduhan daun kelor pada ibu hamil terhadap peningkatan kadar Haemoglobin di UPT Puskesmas Kenali Kecamatan Belalau Kabupaten Lampung Barat Tahun 2021. Jenis penelitian kuantitatif dengan desain quasi eksperimen pendekatan two group pretest and post test design. Populasi ibu hamil 42 orang dengan sampel 30 orang yang dibagi menjadi 2 kelompok masing -masing 15 responden. Objek dalam penelitian pemberian seduhan daun kelor dan kadar Haemoglobin. Penelitian ini telah dilaksanakan di UPT Puskesmas Kenali Kecamatan Belalau Kabupaten Lampung Barat bulan Desember 2021. Pengumpulan data menggunakan lembar observasi. Analisis data secara univariat dan bivariat (uji t test). Hasil penelitian diketahui rata-rata rata-rata kadar Hb sebelum diberikan tablet fe dan seduhan daun kelor pada ibu hamil adalah 10,4 gr/dl dan kadar Hb sesudah diberikan tablet fe dan seduhan daun kelor pada ibu hamil adalah 11,5 gr/dl. Rata-rata kadar Hb sebelum diberikan tablet Fe adalah 10,4 gr/dl, dan kadar Hb sesudah diberikan tablet Fe adalah 10,8 gr/dl. Ada pengaruh pemberian seduhan daun kelor pada ibu hamil terhadap peningkatan kadar Haemoglobin di UPT Puskesmas Kenali Kecamatan Belalau Kabupaten Lampung Barat Tahun 2021 (p-value = 0,000). Saran Memberikan informasi kepada ibu hamil tentang mencegah dan mengantisipasi anemia dengan cara mengkonsumsi seduhan daun kelor